ANALYSIS OF NEEDS FOR DEVELOPING ADAPTIVE-COOPERATIVE LEARNING MODELS TO IMPROVE NUMERACY COMPETENCE AT THE MIDDLE SCHOOL LEVEL - E, Susilawati; S, Muslim; Khaerudin, Khaerudin (International Conference on Humanity Education and Society (ICHES), 2024)
Numeracy competency is one of the characteristics of implementing an independent curriculum. Indonesian students need to strengthen their literacy and numeracy. The needs analysis research aims to determine the level of numeracy achievement at the junior high school level and explore data regarding the need to develop learning models to improve numeracy competency at the junior high school level. The research was carried out using quantitative methods. The research sample was 40 representatives of junior high school teachers spread across western, central, and eastern Indonesia. The results of the research show that based on the AKM (Minimum Competency Assessment) results from respondents, junior high school level numeracy competency is categorized as still low and needs to be improved through the implementation of numeracy-based learning. Aspects of school principal support, teacher readiness, and various ICT infrastructures are potential assets in implementing numeracy-based learning strategies. Developing learning models as part of a strategy to improve students' numeracy competency is very much needed. Therefore, it is necessary to develop an adaptive learning model according to the character and needs of students by integrating ICT according to availability in each school (according to asset-based thinking). This model can also hone students' social skills in communication, cooperation, and collaboration. For future researchers, the results of this research can be used as study material in research on developing learning models to improve numeracy competencies further.